Patients' charters and health responsibilities. Issue 7631 (14th November 2007) - Schmidt, Harald
Abstract : We all have responsibility for our health, the health of others, and to the organisations that provide health care. But, as Harald Schmidt describes, specifying and formalising these duties can create ethical problems